Pengaruh Independensi Dan Gender Komite Audit Terhadap Audit Delay - Nurjanah, Siti (CV. ITTC INDONESIA, 2024)
The influence of audit committee independence and gender on audit delay is the subject of this research. This research was conducted using a quantitative approach combined with a descriptive approach. For this research, the data used was secondary data and the sampling technique used was purposive sampling. This research examines 33 banking companies over a period of 4 (four) years. The results of this research are that independence has a negative effect on audit delay and audit committee gender has a negative effect on audit delay. Therefore, it can be concluded that if the company has an audit committee that is independent then this can reduce the occurrence of audit delays and if the company has more female audit committees then this can reduce the occurrence of audit delays.This research aims to determine the influence of audit committee independence and gender on audit delay.